2020
DOI: 10.1177/2393957519891041
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Man-Know-Man Network Culture Influence Transnational Entrepreneurship?

Abstract: Scholars broadly agree that ethnic network and culture facilitates opportunity formation amongst transnational entrepreneurs (TEs). This article explores shared practices such as cultural values and traditional beliefs in entrepreneurial behaviour to expound how it influences decision-making process amongst TEs. The man-know-man guiding framework is introduced, and scenarios are presented that will allow in-depth understanding regarding how TEs engage in such practices. The article contributes to existing know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Interviewee #28 (Investor) said, "Having something like the Shark Tank TV program will help us investors find the right people and ideas to invest in". Research has shown that networking plays a major role in promoting entrepreneurship and expanding a business at the national and international level [112][113][114].…”
Section: Recommendations For Supporting Agenciesmentioning
confidence: 99%
“…Interviewee #28 (Investor) said, "Having something like the Shark Tank TV program will help us investors find the right people and ideas to invest in". Research has shown that networking plays a major role in promoting entrepreneurship and expanding a business at the national and international level [112][113][114].…”
Section: Recommendations For Supporting Agenciesmentioning
confidence: 99%
“…In addressing savoirvivre, or 'know-how-to-live', AIBXD offers thematic workshops and classes on business networking strategies. These are tailored for various professional profiles and industryspecific audiences, acknowledging that networking nuances can differ across managerial cultures (Njoku and Cooney 2020). Ethical dilemmas and professional conduct are central themes within these learning modules.…”
Section: Integration Of Meccdal's Seven Pillarsmentioning
confidence: 99%
“…Diaspora maintains and sustains connections with their home country, which means that individuals in the diaspora draw on resources and advice from their community. Zapata‐Barrero and Rezaei (2020, p. 1959) refer to diaspora entrepreneurs as “immigrants who are engaged in border crossing business activities involving their country of origin and destination.” This means unlike traditional entrepreneurs, diaspora entrepreneurs utilize the international market in order to develop business activities (Njoku & Cooney, 2020). This enables them to utilize their cultural connections in a positive way that promotes entrepreneurship.…”
Section: Theoretical Frameworkmentioning
confidence: 99%